The testing of listening in bilingual secondary schools of Costa Rica: bridging gaps between theory and practice / Evaluación de la destreza auditiva en los colegios bilingües de Costa Rica: acortando brechas entre teoría y práctica - Gamboa Mena, Roy (Universidad de Costa Rica, 2014)
Despite listening being one of the most crucial skills in the process of communication, research shows that it has been neglected in most English as a Foreign Language (EFL) programs, both worldwide and in Costa Rica. Worse yet, mismatches between theory and practice often result in poor listening assessment in many institutions. Thus, this article examined current listening testing practices by Ministry of Public Education (in Spanish, MEP) in-service teachers ranked C1 according to the Common European Framework (CEF) in bilingual secondary schools of the West Area of Costa Rica. Listening tests created and administered by those teachers were analyzed for their compliance with both theory on listening assessment and MEP’s guidelines on assessment. The study revealed that even though teachers had previously received training on testing, the tests they created do not fully comply with both MEP’s guidelines and theoretical principles on listening assessment. Findings expand conclusions drawn by Gamboa and Sevilla (2013) in previous research on listening assessment and provide several contributions to the current bulk of literature on listening testing practices in Costa Rica. Such conclusions also reveal areas of listening assessment that need to be further tackled through teacher training. Pese a su importancia en el proceso de la comunicación, la habilidad auditiva ha sido ignorada en muchos programas de inglés como lengua extranjera (en inglés, EFL). Peor aún, discrepancias entre teoría y práctica conllevan a un inadecuado proceso de evaluación de esta habilidad lingüística. Ante ello, el presente estudio examina las prácticas en la evaluación auditiva de docentes de inglés en servicio del Ministerio de Educación Pública (MEP) ubicados en la banda C1 según el Marco Común Europeo (en inglés, CEF) en colegios bilingües de la Región de Occidente de Costa Rica. Se analizaron pruebas de escucha diseñadas por el personal docente participante en la investigación en términos de su cumplimiento con la teoría sobre evaluación auditiva y los lineamientos de evaluación del MEP. El estudio reveló que, a pesar de que los docentes habían recibido capacitación en materia de evaluación auditiva, las pruebas que ellos diseñaron no cumplen a cabalidad con los lineamientos de evaluación del MEP ni con los principios teóricos en evaluación auditiva. Los resultados ampliaron conclusiones postuladas por Gamboa y Sevilla (2013) en estudios anteriores sobre el tema y vigorizan el estado de la cuestión sobre la evaluación del componente auditivo en Costa Rica. Dichos resultados también dilucidaron áreas de la evaluación de las destrezas auditivas que aun deben trabajarse mediante la capacitación de docentes.